Chrysophanic Acid Suppresses Adipogenesis and Induces Thermogenesis by Activating AMP-activated Protein Kinase Alpha in vivo and in vitro - Lim, Hara; Park, Jinbong; Kim, Hye-Lin; Kang, JongWook; Jeong, Mi-Young; Youn, Dong-Hyun; Jung, Yunu; Kim, Yong-Il; Kim, Hyun-Ju; Ahn, Kwang-Seok; Kim, Su-Jin; Choe, Seong-Kyu; et al. (Frontiers in Pharmacology, 2016)
Chrysophanic acid (CA) is a member of the anthraquinone family abundant in rhubarb, a widely used herb for obesity treatment in Traditional Korean Medicine. Though several studies have indicated numerous features of CA, no study has yet reported the effect of CA on obesity. In this study, we tried to identify the anti-obesity effects of CA. By using 3T3-L1 adipocytes and primary cultured brown adipocytes as in vitro models, high-fat diet (HFD)-induced obese mice, and zebrafish as in vivo models, we determined the anti-obesity effects of CA. CA reduced weight gain in HFD-induced obese mice. They also decreased lipid accumulation and the expressions of adipogenesis factors including peroxisome proliferator-activated receptor gamma (PPARγ) and CCAAT/enhancer-binding protein alpha (C/EBPα) in 3T3-L1 adipocytes. In addition, uncoupling protein 1 (UCP1) and peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC1α), the brown fat specific thermogenic genes, were up-regulated in brown adipocytes by CA treatment. Furthermore, when co-treated with Compound C, the AMP-activated protein kinase (AMPK) inhibitor, CA was able to restore the activation of AMPKα in both types of adipocytes, indicating the multi-controlling effect of CA was partially via the AMPKα pathway. Given all together, these results indicate that CA can ameliorate obesity by controlling the adipogenic and thermogenic pathway at the same time. On these bases we suggest the new potential of CA as an anti-obese pharmacotherapy.